2018
DOI: 10.4082/kjfm.2018.39.3.155
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age at First Childbirth and Other Factors on Central Obesity in Postmenopausal Women: The 2013–2015 Korean National Health and Nutrition Examination Survey

Abstract: BackgroundWaist circumference is one of the key components of metabolic syndrome. Recent studies demonstrated that the reproductive profile was associated with metabolic syndrome in postmenopausal women. This study focused on the association between central obesity and age at first childbirth. It also considered other factors associated with central obesity in postmenopausal women.MethodsThis study was based on the 2013–2015 Korean National Health and Nutrition Examination Survey and involved 3,143 naturally p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…During pregnancy, the release of corticotrophin releasing hormone from placenta drive the hypothalamic pituitary-adrenal axis and cortisol concentrations in pregnant women may contribute to the pathophysiological mechanism of obesity later in life [78]. But, a recent study conducted among Korean postmenopausal women showed no signi cant association between age at rst childbirth and central obesity after controlling for confounding variables [77]. We found an association between higher incidence of central obesity and higher parity among rural caste participants.…”
Section: Discussionmentioning
confidence: 57%
“…During pregnancy, the release of corticotrophin releasing hormone from placenta drive the hypothalamic pituitary-adrenal axis and cortisol concentrations in pregnant women may contribute to the pathophysiological mechanism of obesity later in life [78]. But, a recent study conducted among Korean postmenopausal women showed no signi cant association between age at rst childbirth and central obesity after controlling for confounding variables [77]. We found an association between higher incidence of central obesity and higher parity among rural caste participants.…”
Section: Discussionmentioning
confidence: 57%
“…During pregnancy, the release of corticotrophin releasing hormone from the placenta drives the hypothalamic pituitary-adrenal axis and cortisol concentrations in pregnant women and may contribute to the pathophysiological mechanism of obesity later in life [ 78 ]. But, a recent study conducted among Korean postmenopausal women showed no significant association between age at first childbirth and central obesity after controlling for confounding variables [ 77 ]. We found an association between higher incidence of central obesity and higher parity among rural caste participants.…”
Section: Discussionmentioning
confidence: 99%
“…13 Given that obesity was a risk factor for lung function 14,15 and age at first childbirth was associated with obesity. 16,17 Moreover, the association between age at first childbirth and lung function has never been discussed in Chinese women. We conducted this study to investigate the association between age at first childbirth and lung function and further test whether the association is mediated by body mass index in a large population of Chinese postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%